SOCIAL ECONOMIC CONDITIONS AROUND THE PALM OIL PLANT COMPANY IN REGENCY - Ira Apriyanti; Muhammad Asyiyami Munthaha (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Changes that made as a result of the establishment of palm oil companies will lead to a positive impact or otherwise will lead to negative things that harm the surrounding community. The purpose of the study is to determine how far the impact of the company's presence on the social and economic conditions surrounding communities. This study aimed to examine the impact caused by the company's presence on the social and economic conditions of people living in locations around the company. This study concluded that the impact of palm oil company's presence in the village Blankahan socially and economically brings many positive effects. The positive impact on social conditions seen in Public Facilities Development, Education, Health and Social Institution against Institutions society. Positive impact on the economic conditions seen in opportunities more to work / strive more at PT. United Kingdom Indonesia Plantations, so as to help the government in reducing unemployment in the village Blankahan.Keywords : Social, Economic, Palm Oil, Community, Unemployment